2018
DOI: 10.1177/1747493018772788
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke social networks, depressive symptoms, and disability in Tanzania: A prospective study

Abstract: Background Evidence suggests that social networks improve functional recovery after stroke, but this work has not been extended to low- and middle-income countries (LMICs). Post-stroke depression interferes with functional outcome but is understudied in LMICs. Aims To determine the relationships between social networks, disability, and depressive symptoms in patients surviving 90-days post-stroke in Dar es Salaam, Tanzania. Methods Participants ≥ 18 years, admitted ≤ 14 days of stroke onset, were enrolled. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 42 publications
3
37
0
1
Order By: Relevance
“…This review found that almost one-third of 1483 stroke survivors (31% pooled frequency) met the cut-offs for depression in the various measures used. Other African prevalence studies confirm that at least one in three stroke survivors will experience PSD (Saadi et al 2018;Sarfo et al 2017b), whilst 1:5 will present with symptoms of severe anxiety (Ojagbemi et al 2017b). Over half will experience cognitive decline as a result of the stroke (Hackett et al 2005).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…This review found that almost one-third of 1483 stroke survivors (31% pooled frequency) met the cut-offs for depression in the various measures used. Other African prevalence studies confirm that at least one in three stroke survivors will experience PSD (Saadi et al 2018;Sarfo et al 2017b), whilst 1:5 will present with symptoms of severe anxiety (Ojagbemi et al 2017b). Over half will experience cognitive decline as a result of the stroke (Hackett et al 2005).…”
Section: Introductionmentioning
confidence: 95%
“…The other three studies all used prospective longitudinal single-cohort designs (Level III-3). Whilst and Gbiri et al (2015) included repeated measures, Saadi et al (2018) only measured participants at two time points.…”
Section: Evidence Gradingmentioning
confidence: 99%
See 3 more Smart Citations